Hassan Hanafi’s new approach to the Koran (Doctor Virtualis, 2022)
Since 1980 we knew that Hasan Hanafi (1935-2021) had a lifelong project that he described as a triangle. The longest side of the triangle is made by his studies on the Islamic heritage and, in particular, on the ʿIlm usūl al-fiqh, The science of the fundamentals of source law. Another side is built by his analysis and criticism of the Western Heritage. The third side concerns true “reality”, and for H. Hanafi reality is the Koran. The article examines his book devoted to this issue: it was his last book.
Keywords: Hasan Hanafi; Qur’ān exegesis; Islamic Jurisprudence; Occidentalism